Influence of AWJM Parameters on Glass/Epoxy Thin Laminate Using Taguchi Analysis - Azmir, M.A.; Ahsan, A.K. (INTI Publishing House Sdn. Bhd., 2006)
Experimental investigations were conducted to assess the influence of abrasive water jet machining (AWJM) parameters on the machining performance criteria namely surface roughness and kerf taper ratio. The approach was based on Taguchi’s Method and Analysis of Variance (ANOVA) to optimize the AWJM parameters for effective machining of woven glass fibre reinforced epoxy composite. It was found that hydraulic pressure, standoff distance, abrasive mass flow rate and cutting orientation were the significant control factors; the cutting orientation was the insignificant control factor in controlling the machining performance criteria. Mathematical models were established using linear regression analysis to predict the surface roughness and kerf taper ratio in terms of the cutting parameters of AWJM. For effective machining of glass fibre reinforced epoxy composites, verification of the improvement in the quality characteristics has been made through confirmation tests with respect to the chosen reference parameter setting. It was confirmed that determined optimal combination of AWJM parameters satisfy the real need for machining of glass fibre reinforced epoxy composites in practice.